Investigating the impact of diversion projects on river health using the spherical fuzzy cloud TOPSIS model and the SHapley Additive exPlanation technique - Ting Cheng; Maosen Ju; Wenhui Zhang; Chenhui Wu; Qi Liu; Qingqing Ban (Ecological Indicators)
Accurate scientific assessments of the impact of water diversion projects on the ecological health of rivers are crucial. We proposed a new integrated framework for river health assessment. First, a three-level indicator system was developed considering both ecological and non-ecological factors, and the indicator weights were calculated using the game combination weighting method. Second, the spherical fuzzy cloud technique for the order of preference by similarity to ideal solution (SFC-TOPSIS) assessment framework was developed and used to analyze the impact of water diversion projects on river health. Finally, the key factors affecting river health were identified using the SHapley Additive exPlanation (SHAP) sensitivity analysis. The results showed that after the completion of the diversion project, the overall health of the river improved from unhealthy to healthy, with a 75% increase in the health compliance rate of the evaluation indicators and a 70% improvement in the health status of the sampling sites. However, the social service functions of the rivers have not yet reached a healthy state. Furthermore, a sensitivity analysis of the indicators of river health showed that the implementation of the water diversion project affected the flood control function and aquatic plant biodiversity indicators of the river. The framework and results proposed in this study are expected to provide support and reference for assessing the impact of other river water diversion projects on river health and sustainable management.